Perilaku Semut dan Laba-Laba dalam Al-Qur’an: Telaah Tafsir Al-Munīr atas Surah al-Naml Ayat 18–19 dan al-‘Ankabūt Ayat 41–42 dalam Perspektif Biologi - Sabrina Rahma; Mhd. Syahminan; Siti Ardianti (Yayasan Albahriah Jamiah Indonesia, 2026)
An integrative study of Qur’anic interpretation and biology is important to broadening understanding of the behavioral phenomena of living creatures mentioned in the sacred text, especially ants and spiders, which have unique social and ecological characteristics. The purpose of this study is to confirm the analysis of the interpretation of Tafsir al-Munīr on Surah al-Naml verses 18–19 and al-‘Ankabūt verses 41–42 and assess its relevance to modern biological findings on communication, colony structure, and survival strategies. The method used is a qualitative literature study based on a thematic interpretation (mawḍūʻī) approach combined with interpretative-critical and comparative analysis to link textual meanings with contemporary scientific data. The results of the study show a significant correspondence between the Qur’anic description of the organized communication system of ants and biological findings related to chemical signals and colony coordination, as well as the depiction of spider webs as fragile structures that align with the material properties of their webs from a scientific perspective. Differences emerge in the symbolic dimension, which enriches ethical and reflective meaning beyond empirical explanation, thus presenting a depth of meaning that science cannot fully grasp. The implications of this study strengthen the contribution of interdisciplinary approaches to the study of interpretation and science, while maintaining the integrity of the text’s theological dimension without reducing its meaning.